Analysis of Factors Shaping the Purchase Decision of Domestically Produced Ultrasound Products in PT. MHJ - Sunardi (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
In order to support the improvement of the domestic medical equipment industry and supporting government programs, PT. MHJ needs to pay attention to what factors create customer purchasing decisions on USG products. This is very important for manufacturers or the domestic medical equipment industry to know, bearing in mind that there are still many negative assumptions about domestically produced goods. The purpose of this study is to find out what factors shape the purchasing decision of this domestically produced USG product. The population of this study were doctors from 10 hospitals and clinics that collaborated with PT. MHJ as many as 3.368 doctors, where the number of research samples was taken using a purposive technique with the criteria of users who want to take their time to fill out the questionnaire so that a total sample of 60 users is obtained. This study used a quantitative approach with a measuring tool in the form of a questionnaire and analyzed using the SPSS program. The results of the study found that there are 7 factors that create the purchase decision of USG products, namely product, supplier, technology, relationship, market, environment, and reliability factors.